GENDER DISPARITIES IN SUICIDAL IDEATION AMONG UNIVERSITY STUDENTS: A QUANTITATIVE STUDY - Razaw Nury Hama Faraj (PsychTech & Health Journal)
This study aimed to investigate gender-based differences in suicidal ideation among KoyaUniversity students. A total of 209 students participated in the study, comprising 104 females and 105 males. A scale for suicidal ideation was adopted to answer the research questions. The research was conducted using a quantitative survey design, and a non-random sampling technique (convenience sampling) was employed to collect the sample. The results indicated a statistically significant difference between males and females regarding suicidal ideation, with a higher prevalence among female students. These findings provide important insights into the issue of suicide among university students in the Kurdistan Region of Iraq.